The female imagination and feminist culture (Journal of the College of Basic Education, 2022)
This research came to shed light on the dominance of masculine culture towards women, who have been marginalized for ages and eras, and this is what prompted them to rebel against that authority as an attempt to raise their voice and get out of the ravage of culture for them, and this is what we will reveal through the poetic image.